USER ACCEPTANCE ANALYSIS OF DANAMAS PEER TO PEER LENDING SERVICES IN DENPASAR CITY - Ni Putu Ratih Parwati; Linda Yupita (Jurnal TAM (Technology Acceptance Model), 2022)
The presence of fintech lending services in the financial sector provides a change in lending and borrowing transactions that were previously still conventionally turned into digital. However, in this facility, there are still some shortcomings that are felt by users in using fintech services. This research is intended to find out what influences users in using fintech services, especially Danamas in Denpasar City by applying the original Technology Acceptance Model (TAM) method which is modified using one external variable. This study uses quantitative methods and data analysis methods using Partial Least Square (PLS) with the help of Smart PLS 3.0 software. The sampling technique in this study uses two techniques, purposive sampling, and area sampling. The results of the tests carried out showed that of the ten hypotheses tested, directly and indirectly, there are seven accepted hypotheses and three rejected hypotheses. The three rejected hypotheses include the relationship between perceived ease of use (Y2) and attitude toward using (Y3), the relationship between perception of security (X1) and actual system of use (Y4) mediated by perceived usefulness (Y1), perceived ease of use (Y1), use (Y2), and attitude toward using (Y3), as well as the relationship between perceived ease of use (Y2) and the actual system of use (Y4) mediated by perceived usefulness (Y1) and attitude toward using (Y3) variables.